2018
DOI: 10.1001/jamadermatol.2018.0793
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Guselkumab Compared With Adalimumab and Placebo for Psoriasis in Specific Body Regions

Abstract: the scalp, palms and/or soles, and nails is challenging to treat.OBJECTIVE To evaluate the effect of guselkumab on psoriasis in specific body regions.DESIGN, SETTING, AND PARTICIPANTS VOYAGE 1 and VOYAGE 2 were, double-blind, placeboand adalimumab-controlled studies of guselkumab conducted at 101 and 115 global sites, respectively, from November 3, 2014, to May 19, 2016. Patients had moderate to severe plaque psoriasis (Psoriasis Area and Severity Index score Ն12, Investigator's Global Assessment [IGA] score Ն… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 33 publications
(93 reference statements)
3
81
0
11
Order By: Relevance
“…New biologic agents such as risankizumab [11], guselkumab [12][13][14][15][16], ixekizumab [17][18][19][20][21][22][23], and brodalumab [24,25] demonstrated high efficacy for patients with moderate-to-severe psoriasis. The percentage of patients who achieved more than a 90% reduction in the Psoriasis Area Severity Index (PASI) score at 16 weeks after initiating each treatment (PASI 90) was about 70%-80%, and that at 52 weeks was about 80%-90% in respective clinical trials.…”
Section: Plaque Psoriasismentioning
confidence: 99%
“…New biologic agents such as risankizumab [11], guselkumab [12][13][14][15][16], ixekizumab [17][18][19][20][21][22][23], and brodalumab [24,25] demonstrated high efficacy for patients with moderate-to-severe psoriasis. The percentage of patients who achieved more than a 90% reduction in the Psoriasis Area Severity Index (PASI) score at 16 weeks after initiating each treatment (PASI 90) was about 70%-80%, and that at 52 weeks was about 80%-90% in respective clinical trials.…”
Section: Plaque Psoriasismentioning
confidence: 99%
“…Two multicenter, randomized, double-blind, placebo-and comparator-controlled clinical trials (VOYAGE 1 and VOYAGE 2) showed significantly greater improvements from baseline with guselkumab versus placebo (weeks 8 and 16) and versus ADA (week 24) [38]. A secondary analysis revealed that patients on guselkumab showed significant improvement in PsO of the scalp and palms and/or soles compared to patients on ADA, but the magnitude of improvement did not differ between the 2 treatments in patients' fingernails [39].…”
Section: Guselkumabmentioning
confidence: 99%
“…From an efficacy perspective, we recommend in psoriasis patients with nail disease the TNF antagonists: infliximab, adalimumab, certolizumab pegol and etanercept; the IL12/23 inhibitor: ustekinumab; the IL23/ p19 inhibitors: guselkumab and risankizumab; the IL17 receptor blocker: brodalumab; the IL17 inhibitors: ixekizumab and secukinumab; and the synthetic drug, apremilast. [64][65][66][67] Also, the conventional drugs dimethylfumarate, cyclosporine and methotrexate are used based on clinical trial data. There is less robust evidence supporting the use of the conventional drugs cyclosporin, methotrexate and acitretin; however, it is our opinion that these drugs also provide benefit to psoriasis patients with nail disease especially in patients with limited skin involvement (PASI/BSA < 10).…”
Section: Clinical Recommendationsmentioning
confidence: 99%